2011 IEEE 37th Annual Northeast Bioengineering Conference (NEBEC) 2011
DOI: 10.1109/nebc.2011.5778712
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance-based biopsy for prostate cancer detection

Abstract: Currently biopsy is considered the gold standard for diagnosis of prostate cancer in humans, although it samples only 19mm 3 volume of prostate, corresponding to 0.95% of a 50cm 3 prostate gland for a regular 12-core biopsy procedure. The aim of this study was to increase the sampling volume by incorporating electrical impedance spectroscopy (EIS) into the standard biopsy needle. Electrical impedance can act as a reliable biomarker for distinguishing malignant from benign tissues in human prostate. The EIS bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 2 publications
0
10
2
Order By: Relevance
“…An insulating polyimide sheath (Miniature Polyimide Tubing, 0.810 mm ID, 0.861 mm OD, Part Number: SWPT-0319-30) was applied onto the surface of the needle (0.643 mm OD × 254 mm, Myco Medical, Reli Chiba Point Needles, CHE22G101) leaving only the tip of the needle (2 – 3 mm) uncovered [12]. The other end of the needle was connected to the TREIT data acquisition system (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…An insulating polyimide sheath (Miniature Polyimide Tubing, 0.810 mm ID, 0.861 mm OD, Part Number: SWPT-0319-30) was applied onto the surface of the needle (0.643 mm OD × 254 mm, Myco Medical, Reli Chiba Point Needles, CHE22G101) leaving only the tip of the needle (2 – 3 mm) uncovered [12]. The other end of the needle was connected to the TREIT data acquisition system (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The electrodes placement was done to create a restricted electric field in the prostate area and get more reliable results in terms of sensitivity as demonstrated by other authors. [7,8,11,12]. The novel probe was conceived to test the prostate tissue directly and consists of an electrode placement over a single rubber finger glove tip wearable over the rubber gloves normally used to detect prostate abnormalities.…”
Section: The Bia Test and The New Endo Rectal Probementioning
confidence: 99%
“…Previous studies on BIA revealed enthusiastic results mainly in patients with aggressive cancers [5][6][7]. Studies conducted in the setting of prostate cancer in particular, were limited by the applicability of proper probes on the prostate gland surface and by the anatomic deep site in which the prostate is placed inside the pelvic bone girdle [8]. With the aim to reduce previous limitations in the applications of BIA test, we tested the performance of a novel endorectal probe in a series of consecutive patient candidate to prostate biopsy for suspicious prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The EISBx has radial and axial sensitivities of ~4mm and ~3mm, respectively [9]; because the probe was inserted sufficiently deep into the prostate (>4 mm), the saline solution surrounding the tissue did not have a significant influence on the measurements. The extracted biopsy sample is microtomed, stained with H&E, and microscopically evaluated by a pathologist to determine if benign or malignant cells are present in tissue core (Figure 3).…”
Section: Preclinical Ex-vivo Evaluationmentioning
confidence: 99%
“…We have developed an electrical impedance spectroscopy (EIS) sensing biopsy (Bx) needle to record bipolar impedance measurements in tandem with tissue core extraction. We have demonstrated that this type of data has the potential to distinguish normal from abnormal tissue across a larger fraction of prostate volume than that sampled during conventional biopsy procedure [8] [9]. We present our most recent analysis of a 27 patient cohort evaluating how well these electrical properties discriminate cancer from non-cancer tissues in the prostate.…”
Section: Introductionmentioning
confidence: 99%